2012
DOI: 10.1021/mz300486h
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 1H NMR Analysis of Chemical Stabilities in Anion-Exchange Membranes

Abstract: We compared the alkaline stability of three classes of anion exchange membranes that are leading candidates for applications in platinum-free fuel cells. A methodology is presented for the study of chemical stability of anion-exchange polymers in alkaline media that provides clear and quantitative 1H NMR spectroscopic data of dissolved polymers containing benzyltrimethylammonium functionalities. Recent studies have investigated the stabilities of benzimidazolium- and alkylimidazolium-bearing polymers using per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
156
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(157 citation statements)
references
References 24 publications
1
156
0
Order By: Relevance
“…Hydroxide degradation rates increase with decreasing dielectric constant, 29 like those found in organic solvents. 11,12 The nucleophilicity of the hydroxide anion increases in the lower dielectric constant media and the observed increase in degradation rate may simply be due to partitioning of some fraction of BTMA and hydroxide into the organic phase accompanied by accelerated degradation rates. Additionally the possibility exists that the organic phase components also participate in degradation reactions thereby increasing degradation rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxide degradation rates increase with decreasing dielectric constant, 29 like those found in organic solvents. 11,12 The nucleophilicity of the hydroxide anion increases in the lower dielectric constant media and the observed increase in degradation rate may simply be due to partitioning of some fraction of BTMA and hydroxide into the organic phase accompanied by accelerated degradation rates. Additionally the possibility exists that the organic phase components also participate in degradation reactions thereby increasing degradation rates.…”
Section: Resultsmentioning
confidence: 99%
“…Degradation of BTMA has been the subject of several past studies. 5,[9][10][11][12][13] However, methodologies of degradation were not standardized or fully validated. Several reports that include BTMA degradation are presented in Table I to highlight the differences in reaction conditions and use of various experimental techniques.…”
mentioning
confidence: 99%
“…To overcome this challenge, various functional groups such as imidazole [6,7], guanidine [8], trimethylamine [9e11], benzimidazole [12], and phosphine [13] were usually used for synthesis of alkaline AEMs. Unfortunately, as revealed by the computational and experimental studies, the alkyl chain structure and structure around b hydrogen are more sensitive to degradation conditions and Hofmann elimination [14,15]. Cationic degradation causes the reduction in hydroxide conductivity and ion exchange capacity of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic degradation causes the reduction in hydroxide conductivity and ion exchange capacity of the membrane. This type of degradation was observed by 1 H NMR spectroscopy and Fourier transforms infrared spectroscopy [15]. Amduri's group found that synthesis of alkaline anion exchange membrane without hydrogen at b position to quaternary nitrogen could minimize membrane decomposition and Hofmann elimination [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This polymer has been an excellent platform for AEM development due to its ease of chemical modification and large-scale synthesis. However, poly(phenylene oxide) is susceptible to degradation under the most stringent conditions of high temperature (above 80 °C) and high pH (1-4 M NaOH) 31 and under oxidative conditions. 32 Under milder conditions at 60 °C, many materials have demonstrated high pH stability, so it is difficult to find the most promising materials using low-temperature degradation measurements.…”
Section: Strategies For Developing New Anion Exchange Membranes and Ementioning
confidence: 99%